Mendorong Kinerja Batik Biru Lancor dengan Meningkatkan Kualitas Produk, Kapasitas Produksi dan Inovasi Motif - Tedy Herlambang; Mutinda Teguh Widayanto (Jurnal Pengabdian Masyarakat Sains dan Teknologi, 2024)
This community service aims to improve the quality of Biru Lancor Batik in Probolinggo by producing print batik and more variation in batik motifs. Batik craftsmen were also given training to improve their knowledge and skills in the batik business. This activity provides positive results in term of increased quality, production capabilities and managing the performance of batik businesses. To achieve a sustainable business, further service can be focused on developing knowledge and skills in processing batik waste, using dyes from environmentally friendly materials such as twigs, leaves, stems and flowers collected from surrounding, creating batik motifs that reflect environmental conservation and creating a work environment that is safer and more comfortable.